2011
DOI: 10.1242/jeb.058420
|View full text |Cite
|
Sign up to set email alerts
|

Scaling of resting and maximum hopping metabolic rate throughout the life cycle of the locust Locusta migratoria

Abstract: Secondly, a recent comparative analysis concludes that insect metabolic rate does scale with a k-power exponent (Riveros and Enquist, 2011), and the authors use this as evidence to provide broad . Increasing body mass by 20-45% with attached weights did not increase mass-specific MM O2 significantly at any life stage, although mean mass-specific hopping M O2 was slightly higher (ca. 8%) when juvenile data were pooled. The allometric exponents for all measures of metabolic rate are much greater than 0.75, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 59 publications
(83 reference statements)
2
35
2
Order By: Relevance
“…There was also no significant difference between the body mass of adult locusts used in the present study and those used in earlier respirometry experiments (ANOVA, P0.21) (Snelling et al, 2011a;Snelling et al, 2012). Nevertheless, body-mass-specific values are presented (except for volume density, surface density and thickness estimates).…”
Section: Body Masscontrasting
confidence: 52%
See 4 more Smart Citations
“…There was also no significant difference between the body mass of adult locusts used in the present study and those used in earlier respirometry experiments (ANOVA, P0.21) (Snelling et al, 2011a;Snelling et al, 2012). Nevertheless, body-mass-specific values are presented (except for volume density, surface density and thickness estimates).…”
Section: Body Masscontrasting
confidence: 52%
“…The flight muscles contain predominantly fast phasic-type fibres (Kutsch and Usherwood, 1970;Mizisin and Ready, 1986;Wilson and Weis-Fogh, 1962), whereas the hopping muscles contain a mixture of fast phasic-type, slow tonic-type and intermediate-type fibres (Cochrane et al, 1972;Hoyle, 1978). Earlier respirometry revealed that the maximum oxygen consumption rate of adult hopping muscles during jumping exercise averages 158molh -1 g -1 body mass (Snelling et al, 2011a), whereas the flight muscle consumes a maximum of 967molh -1 g -1 during tethered-flight exercise (Snelling et al, 2012). According to the principles of symmorphosis, the 6.1-fold difference in aerobic capacity between the hopping and flight muscles should be matched by an equivalent difference in the overall volume, surface area and anatomical diffusing capacity of the tracheoles in the two muscles, and also in the total volume and inner membrane surface area of the mitochondria in the two muscles.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations